PENGUKURAN PERUBAHAN SUDUT POLARISASI PADA KOLESTEROL SEBAGAI KOREKSI PADA MINYAK SAWIT - Ulfa Maftukhah; Ketut Sofjan Firdausi (Youngster Physics Journal, 2016)
This research aims to determine the relation between changes of polarization angle and increased levels of cholesterol and triglycerides on palm oil (expired palm oil, edible palm oil) to the change of polarization angle. Samples were placed on a polarimeter with a light source of 100 W incandescent lamp. The results showed that the increase in the cholesterol is directly proportional to the change in polarization angle. The greater increase of cholesterol levels result in the greater of the change of polarization angles that showed in the non linier graph. The value of the change of polarization angle in expired palm oil, edible palm oil are θ cholesterol = 0,26⁰; 0,25⁰ for cholesterol and θ triglycerides = 1,19⁰ ; 0,6⁰ for triglycerides, respectively. So it can be seen that the increase of each change of polarization angle of triglyceride which is the difference of θ total with θ cholesterol are affected by the increase of cholesterol levels in the cooking oils. The volatile property of the solvent and the less stabil environment temperature also could affected the result of the study.